Frontal Face Detection using Haar Wavelet Coefficients and Local Histogram Correlation - Setyawan, Iwan; Timotius, Ivanna K.; Febrianto, Andreas A. (Journal of ICT Research and Applications, 2013)
Face detection is the main building block on which all automatic systems dealing with human faces is built. For example, a face recognition system must rely on face detection<!--[if supportFields]><spanlang=EN-US> XE "facedetection" <![endif]--><!--[if supportFields]><spanstyle='mso-element:field-end'><![endif]--> to process an input image and determine which areas contain human faces. These areas then become the input for the face recognition system for further processing. This paper presents a face detection system designed to detect frontal faces. The system uses Haar wavelet coefficients and local histogram correlation<!--[if supportFields]><spanlang=EN-US> XE "localhistogram correlation" <![endif]--><!--[if supportFields]><spanlang=EN-US><![endif]--> as differentiating features. Our proposed system is trained using 100 training images. Our experiments show that the proposed system performed well during testing, achieving a detection rate of 91.5%.